2019
DOI: 10.1177/1687814019889801
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic functional surface of reducing soil adhesion on 65Mn steel

Abstract: The phenomenon of soil adhesion occurs when soil-tillage implements interact with soil, which often increases the working resistance and energy consumption. It was found that the membranous leaf sheath of rhizoma imperatae can shuttle in soil, owing to not only its own growth force, but also the anti-adhesion function due to the hydrophobicity and special surface texture. In this article, the microstructure and surface wettability of membranous leaf sheath were studied to reveal its anti-adhesion property by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…Due to the reduction in soil adhesion, its traction resistance decreased by 2.13–22.30% at a speed of 1.04 m/s. Li et al [ 130 ] found that the anti-adhesion performance of the membranous leaf sheath surface was the result of the joint interaction of surface structure and hydrophobicity. Based on this, bionic specimens with various structures were designed.…”
Section: Biomimetic Soil-engaging Componentsmentioning
confidence: 99%
“…Due to the reduction in soil adhesion, its traction resistance decreased by 2.13–22.30% at a speed of 1.04 m/s. Li et al [ 130 ] found that the anti-adhesion performance of the membranous leaf sheath surface was the result of the joint interaction of surface structure and hydrophobicity. Based on this, bionic specimens with various structures were designed.…”
Section: Biomimetic Soil-engaging Componentsmentioning
confidence: 99%
“…The theory of profiling design and non-smooth surface drag reduction has been rapidly developed and applied and also has been widely recognized [9,10]. The non-smooth surface structure also has a good anti-adhesion and desorption effect on the soil-engaging components of agricultural machinery, such as the structure of convex hulls, pits, and ribs [11,12]. Numerous studies have shown that the shape, depth, and density of surface textures have a significant impact on friction, but under different working conditions such as pressure and load, they can affect the effect of a surface structure and even lead to its failure [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…65Mn steel, renowned for its exceptional strength, toughness, and wear resistance, finds widespread application in the fabrication of soil-engaging components for agricultural machinery, including tine harrows, plowshares, and deep-pine shovels [1][2][3]. However, during operational usage, these components often encounter harsh conditions such as elevated temperatures, heavy loads, and the absence of lubrication, leading to severe wear and fatigue [4]. Conventional 65Mn steel presents challenges in further enhancing its performance.…”
Section: Introductionmentioning
confidence: 99%